Gapu-Monak Saltwater: Journey to Sea Country Exhibition Site Visit to the Australian National Maritime Museum (NEW: Emerging scholars in Australian Indigenous Studies, 2019)
Community. One of the key words that resonated with me during my site visit to the Australian National Maritime Museum for the Gapu-Monuk Saltwater: Journey to Sea Country Exhibition. As I walked towards the entrance of the building, the image of Djambawa Marawili Am, renowned Indigenous artist and elder, immediately caught my attention. A quote above his image read:It is time for non-Aboriginal people to learn about this land, learn about the waters. So if we are living the way of reconciliation, you must learn about Native Title and Sea Right. It was my time to be educated and informed, and the right time was now.